2009
DOI: 10.1086/597227
|View full text |Cite
|
Sign up to set email alerts
|

Home Range and Parasite Diversity in Mammals

Abstract: Parasite diversity among and within host species is not solely the result of random processes; rather, it depends on a suite of physiological or ecological host traits as well as environmental factors. Because most macroparasites exhibit life cycles that include infective stages off the definitive host and that rely on host movements for dissemination, parasite acquisition by a host depends largely on hosts being present in a given area where and when infective stages are present. Consequently, host ranging pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 49 publications
1
61
0
Order By: Relevance
“…feeding ecology, habitat preferences, host age and sex, richness of host species in the area) and abiotic (e.g. humidity, temperature) factors can affect the spatial and temporal distribution of parasite species richness by influencing the survival and/or transmission of parasites (Behnke et al 1999, Abu-Madi et al 2000, Bordes et al 2009). The trophic niches of A. agrarius and A. flavicollis are similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…feeding ecology, habitat preferences, host age and sex, richness of host species in the area) and abiotic (e.g. humidity, temperature) factors can affect the spatial and temporal distribution of parasite species richness by influencing the survival and/or transmission of parasites (Behnke et al 1999, Abu-Madi et al 2000, Bordes et al 2009). The trophic niches of A. agrarius and A. flavicollis are similar.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Bordes et al (2009), by focusing on helminths in wild mammals, found a negative correlation between home range area and parasite species richness in carnivores and glires. Male home ranges generally exceed those of females in small-mammal populations, particularly during the breeding season (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…with other hosts will influence pathogen transmission (Morgan et al 2006, Bordes et al 2009). Intra-and inter-species mixing, the presence or absence of particular species, and the proportion of juveniles in the population vary seasonally for waterfowl and are important influences on the ecology of infectious diseases (Wallensten et al 2007).…”
Section: Aiv -Avian Influenza Virus Rfs -Ecological Risk Factorsmentioning
confidence: 99%
“…data). Maintaining large home ranges and low densities is a life history strategy that allows caribou to avoid detection and predation by wolves and other predators (Bergerud, 1992), and limit exposure to parasites which influence body condition and fitness (Bordes et al, 2009;Gunn & Irvine, 2003). Fragmentation and direct or effective loss of available habitat as a result of anthropogenic change has been linked to range loss and caribou extirpation (e.g., Schaefer, 2003;Vors et al, 2007).…”
Section: Discussionmentioning
confidence: 99%